Upaya pencegahan resiko disfungsi keluarga melalui permainan kotak edukasi berbasis Talking Pen - Niki Moktika Dwi Megawati; Reynanda Putra Pratama; Nisriani Uswatunnisa; Putri Wandana; Ahmad Dzaky Zain; Adi Irawan Setiyanto (Pusat P2M Politeknik Negeri Batam, 2020)
One aspect of outcome in national expansion is the development of a prosperous family (UU No. 52 year 2009). Each parent is obliged to care, educate, guide the lives of children to adulthood. Therefore, in the PP No. 21 year 1994 family function includes functions of religion, social and cultural, affection, protection, socialization and education, economic and environmental development. The purpose of carrying out this program, specifically: 1) Provides additional knowledge about the function and role of family through educational games